Resilience to water deficit of coffee seedlings produced through cuttings and somatic embryogenesis - Anderson William Dominghetti; Tainah Freitas; Helbert Rezende de Oliveira Silveira; Rubens José Guimarães (Revista Ceres)
ABSTRACT Information on Coffea arabica L. vegetatively propagated during crop establishment is still scarce. Knowledge on the anatomical and physiological adaptation of these types of plants in the crop formation phase, in conditions of water deficit is important. The objective of this work was to understand the anatomical and physiological adaptations of plants derived from cuttings and somatic embryogenesis as resilience to water deficit in the implantation phase of the crop. Both types of plants were submitted to 20%, 40%, 60%, 80% and 100% of water available in the soil, in a controlled environment, for 153 days. The design used in this experiment was the randomized blocks with five replications. Physiological characteristics (photosynthetic activity, stomatal conductance, transpiration and instantaneous carboxylation efficiency) and anatomical characteristics (palisade parenchyma thickness and stomatal density) were evaluated. Both types of plants are resilient to water deficit in the planting phase of the crop. Cutting plants have greater photosynthetic activity and palisade parenchyma thickness with greater growth potential. In general, somatic embryogenesis plants have higher stomatal density. Plants of both types of seedlings have lower values of transpiration, stomatal conductance and CO2 assimilation under water deficit conditions, but with higher stomatal densities, as an adaptation response.